2010
DOI: 10.1253/circj.cj-10-0197
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Left Atrial Mechanical Dysfunction Predicts Postoperative Atrial Fibrillation After Coronary Artery Bypass Graft Operation - A Velocity Vector Imaging-Based Study -

Abstract: Background:The aim of the present study was to evaluate pre-existent subclinical mechanical atrial dysfunction in patients with postoperative atrial fibrillation (POAF) by using novel echocardiographic techniques. Methods and Results:Ninety-six patients with sinus rhythm, undergoing coronary artery bypass graft (CABG) operation were prospectively enrolled. Preoperative left atrial (LA) reservoir, conduit and booster functions were evaluated by 3 different methods: conventional echocardiography, tissue Doppler … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 26 publications
0
30
0
Order By: Relevance
“…Benedetto et al in their study of patients undergoing CABG, proved that peak atrial systolic mitral annular tissue Doppler velocity <9 cm/sec could predict AF. 43 44 Previous studies have recently demonstrated that global PALS, which reflects the passive stretching of the left atrium during LV systole, is an accurate measurement of LA reservoir function. Speckle tracking echocardiography, by which tissue markers (speckles) are tracked from frame to frame throughout the cardiac cycle, has been recently used for evaluation of myocardial deformation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Benedetto et al in their study of patients undergoing CABG, proved that peak atrial systolic mitral annular tissue Doppler velocity <9 cm/sec could predict AF. 43 44 Previous studies have recently demonstrated that global PALS, which reflects the passive stretching of the left atrium during LV systole, is an accurate measurement of LA reservoir function. Speckle tracking echocardiography, by which tissue markers (speckles) are tracked from frame to frame throughout the cardiac cycle, has been recently used for evaluation of myocardial deformation.…”
Section: Discussionmentioning
confidence: 99%
“…Teyyaraci et al in their study of patients undergoing CABG, VVI-based LA strain, systolic strain rates and early diastolic strain rate were independent predictor of POAF. 43 Again, Gabriella et al studied patients undergoing CABG demonstrated that STE-based LA strain and strain rate were lower in patients who developed POAF. 17 Cameli et al followed 197 patients with mitral regurgitation, and found that those who developed paroxysmal AF had lower global atrial longitudinal strain (16.3 AE 2.9 vs. 33.9 AE 4.4; P < 0.05).…”
Section: Discussionmentioning
confidence: 99%
“…[25][26][27] However, this technique is available only in the 2D mode of TTE, is difficult to use in the evaluation of vortex, and is limited in terms of sub-optical images in patients with obesity or emphysema. 4D-Flow can clearly and non-invasively measure all 3D components of the vectors of blood velocity relative to all 4 spatio-temporal dimensions of the heart and great vessels, which has otherwise been difficult in TTE.…”
Section: Imaging Of the Intra-la Vortex With 4d-flowmentioning
confidence: 99%
“…Traditional approaches assessing atrial remodeling is conventional echocardiography in clinical practice [8,23]. A widely used parameter of assessing LA remodeling by echocardiography is LA Anterior-Posterior diameter in the parasternal long-axis view [7].…”
Section: Discussionmentioning
confidence: 99%
“…Because of the combination of speckle tracking (a series of unique B-mode pixel tracking algorithms), mitral annulus motion and tissue-blood border detection, VVI show more feasible and reproducible in assessing LA remodeling status of very thin atrial wall, compared with other echocardiographic methods [7], recently been applied to the evaluation left atrial mechanical dysfunction in coronary artery disease patients [8], regional myocardial dysfunction in patients with acute myocardial infarction [27], have emerged as a quantitative technique for the estimation of myocardial structure and function. Especially, LA strain derived from the VVI is inversely related to LA wall fibrosis, a key hallmark of LA remodeling.…”
Section: Discussionmentioning
confidence: 99%